Direct observation of site-specific dopant substitution in Si doped (AlxGa1−x)2O3 via atom probe tomography. (22nd February 2021) - Sarker, Jith; Bhuiyan, A F M Anhar Uddin; Feng, Zixuan; Zhao, Hongping; Mazumder, Baishakhi
Abstract: In this work, the interaction of n-type dopants in Si doped (Al x Ga1− x )2 O3 films with varying Al content over the entire composition range ( x = 0%–100%) was analyzed using atom probe tomography. An almost uniform dopant distribution with dopant density in the range of 10 18 cm −3 was obtained in (Al x Ga1− x )2 O3 layers with Al contents, x < 0.60. At x ⩾ 0.6, small Si segregated zones were observed which was attributed to the increased donor-acceptor transition centers or bond length differences in Al–O, Ga–O and Si–O at high Al content. We have demonstrated that for the single phase β -(Al x Ga1− x )2 O3 films with Al content of x < 0.30, dopants prefer to occupy on Ga sites while Al site is preferred for high Al content ( x > 0.50) (Al x Ga1− x )2 O3 layers. It was also observed for Al content, x = 0.30–0.50, no specific cationic site occupancy was observed, Si occupies either Al or Ga sites. This can be attributed to highly inhomogeneous layers within this Al composition range due to which dopant Si atoms are either in the Al-rich or Al-depleted regions.